A Narrative of the Troubles in the Second Church in Windsor, 1735–1741 - Mullen, Lincoln A. (Jonathan Edwards studies, 2012)
In 1740-41, the laypeople of the Congregational church in East Windsor drew up a lengthy document, "A Narrative of the Troubles in the Second Church in Windsor, 1735-1741." The narrative describes a six-year conflict within the church, and embedded within it are letters, church records, and the proceedings of church councils relating to the affair. The dispute was between the Rev. Timothy Edwards and his supporters, on the one one hand, and a party of the laity headed by the future Connecticut governor Roger Wolcott, on the other. At stake were two issues: first, what powers belonged to the minister and to the membership in cases of church discipline, and by what procedures those powers should be exercised; second, whether one Joseph Diggins could be barred from owning the covenant, and thus whether his children could be barred from baptism. The "Narrative" is a sustained statement by the East Windsor laity of their concerns about church government, the sacraments, marriage, and relations to their minister. The congregation, which also left behind a number of conversion relations, was no "silent democracy" in the face of a "speaking aristocracy"; rather, they offered a comprehensive defense of their position from Scripture, New England practice, and analogy to politics. Just as the congregation put their arguments in the context of the history of the New England Way, so it is necessary to recount the history of Congregational church government in the Connecticut River Valley before examining the East Windsor church during Timothy Edwards’s pastorate and the content of the "Narrative" itself.